ADAPTING GLOBAL HR PRACTICES FOR ENTERPRISES IN UZBEKISTAN - Asqarova Feruzaxon Shuxrat kizi (European Science Publishing, 2025)
The increasing globalization of business has propelled organizations to adopt universal human resource practices to enhance efficiency and competitiveness. However, the distinct cultural, economic, and legal landscape in Uzbekistan requires companies to thoughtfully adapt these global practices. This article examines the necessity for enterprises in Uzbekistan to localize their HR strategies to align with international best practices while also reflecting the unique characteristics of the local workforce. By focusing on elements such as cultural adaptation, talent acquisition, and employee engagement, the study provides insights into how businesses can successfully navigate the complexities of human resource management in Uzbekistan.
Keywords: global HR practices, Uzbekistan, human resource management, cultural adaptation, strategy, employee engagement, localization